Supply chain management in horticultural nursery business - Rajasree, P.; Prema, A.; Ajith Kumar, K.; Indiradevi, P. (Journal of Tropical Agriculture, 2017)
The importance of horticulture sector in our economy is increasing over the years. This has necessitated the need for quality seeds and planting materials which in turn has increased the importance of horticultural nursery business. This study analyses the supply chain management of horticultural nurseries and constraints in nursery business in Thrissur district, which is considered as the hub of nursery business in Kerala. The random sample survey conducted among the nursery owners showed that nearly 3/4th of the nurseries were unregistered. Supply chain mapping identified two major categories of supply chains i.e., supply chain of plants produced in the nursery and supply chain involving plants purchased from other nurseries. Supply Chain Performance Index (SCPI) of plants produced in the nursery was 0.86 and that of plants purchased from other nurseries was 0.80. The BC ratio of large scale nurseries was 1.92, followed by medium scale nurseries 1.65 and small scale nurseries 1.56. The major constraints in nursery business as reported by the nursery owners in the study area were market rivalry, non-availability of raw materials and cost of raw materials.